Objetos de metal musealizados: uma proposta de metodologia de intervenção curativa - Oliveira, Eder Ribeiro (2018)
The present study presents the research and consequent experimentation in order to establish a curative intervention capable of removing rust accumulated by the natural phenomenon from the oxidation of musealized metal objects, in a safe, ethical, responsible and financially accessible way for museums and institutions preservation. The research arose in the search for a method that could satisfy the needs of special care for museum cultural assets of the Museu Antropológico Diretor Pestana, presenting to museum professionals a new possibility comprised between preventive conservation practices and restoration interventions. In order to do so, a dense bibliographical research was carried out, a revision of museological documentation, a council of preventive conservation manuals, a search for methods used in many activities aimed at the preservation of metallic objects, popular knowledge in the treatment of metals, and the confluence of fields of knowledge, such as Cultural Heritage, Restoration, Chemistry and Museology. Experiments were performed in the MADP processing room with several common metal bodies from different alloys, comparing results and refining strategies before submitting the components of the collection to the methodology. A evaluation of the conservation status of the selected objects of the collection was carried out, and finally the method was applied to illustrate the study with the metallic alloys components and to draw a comparative between the instances. The conclusion of the work brings reflections on the cultural asset that has undergone intervention and presents in the appendix a practical guide of how to proceed with the application of curative intervention methodology.